1988
DOI: 10.1099/00222615-26-2-101
|View full text |Cite
|
Sign up to set email alerts
|

The effect of campylobacter lipopolysaccharide on fetal development in the mouse

Abstract: Summary. Purified lipopolysaccharide (LPS) obtained from isolates of Campylobacter fetus ss. fetus and Campylobacter jejuni impaired fetal development when administered to mice on day 13 of pregnancy. Strikingly more fetal resorption was produced by C. jejuni LPS than by similar amounts of C. fetus ss. fetus LPS. Three of the four Campylobacter strains examined produced LPS that had no effect on maternal health, but LPS from one C. jejuni strain killed all of the mice to which it was administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…In addition LPS may also affect directly the embryo since it is able to cross the placental barrier. In fact, it was demonstrated that, in rat, maternal LPS administration induces an increased expression of IL-1 and TNF-mRNA in the fetal brain [21], as well as it was reported that maternal bacterial infection or LPS administration induces preterm labor and delivery or foetal death and abortion [22][23][24][25]. We have previously demonstrated in an avian model that LPS is able to affect both the mechanical activity of the embryonal heart and the viability of cultured cardiomyocytes [26] and that the presence of CD14 on embryo cardiomyocytes surface plays a pivotal role in the LPS up-take and subsequent functional responses [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition LPS may also affect directly the embryo since it is able to cross the placental barrier. In fact, it was demonstrated that, in rat, maternal LPS administration induces an increased expression of IL-1 and TNF-mRNA in the fetal brain [21], as well as it was reported that maternal bacterial infection or LPS administration induces preterm labor and delivery or foetal death and abortion [22][23][24][25]. We have previously demonstrated in an avian model that LPS is able to affect both the mechanical activity of the embryonal heart and the viability of cultured cardiomyocytes [26] and that the presence of CD14 on embryo cardiomyocytes surface plays a pivotal role in the LPS up-take and subsequent functional responses [27].…”
Section: Introductionmentioning
confidence: 99%
“…Humans are constantly exposed to low levels of LPS through microbial infections. Systemic maternal LPS exposure has been previously shown to be associated with adverse fetal developmental outcomes such as embryonic resorption, intrauterine fetal death, and preterm labor in animals (6). In addition, microbial invasion of the placenta is reported to cause chorioamniotitis and preterm labor in human patients (1).…”
mentioning
confidence: 99%
“…, 2006). In animal models, C. jejuni and C. fetus infections result in impaired fetal development and IUGR (O’Sullivan et al. , 1988a,b).…”
Section: Discussionmentioning
confidence: 99%